PENGARUH KONSENTRASI DAN LAMA PERENDAMAN ZAT PENGATUR TUMBUH (ZPT) ALAMI EKSTRAK DAUN KELOR TERHADAP PERTUMBUHAN BIBIT TEBU (Saccharum Officinarum L.) BUD SET - Hartini Hartini (Jurnal Ilmiah Media Agrosains, 2021)
Moringa plants have many compounds that can be used as medicine or used to stimulate plant growth. Moringa plants contain growth hormones, namely cytokinins and zeatin. The utilized Moringa leaves as a natural or organic growth regulator that can be affect plant growth. This study aims to determine the use of Moringa leaves as a natural ZPT and the length of soaking for the growth of sugarcane bud sets for researchers themselves or those who read this research report. The research was conducted at the LPP Polytechnic Practice Garden, Wedomartani Village, Sleman Regency, Yogyakarta from January to June 2020 (7 months). Experiments were arranged in a factorial randomized block design (RBD). The first factor was giving the concentration of Moringa leaf extract which consisted of 4 treatments, namely: without giving Moringa leaf extract (K0), 10% (K1), 20% (K2), and 30% Moringa leaf extract (K3). The second factor is the immersion time of Moringa leaf extract which consists of 4 treatments, namely: without soaking Moringa leaf extract (R0), 10 minutes (R1), 20 minutes (R2), and 30 minutes (R3). There were 16 treatment combinations and was repeated 3 times so that there were 48 experimental units. Each experimental unit consisted of 2 plants so that there were 96 plants in total. The results showed that there was no interaction between the concentration of Moringa leaf extract treatment and the duration of soaking. Giving the concentration of Moringa leaf extract and the duration of soaking did not occur any interaction between the two treatments and had a single significant effect, namely the concentration on several variables, namely plant height, stem diameter, wet weight and dry weight. Giving the concentration of Moringa leaf extract as much as 20% produced plant height, stem diameter, number of leaves with wet weight and dry weight were higher than without giving moringa leaf extract. Key words: bud set, concentration, growth regulatory substance, immersion